Acute inflammatory reaction during anti-angiogenesis therapy combined with immunotherapy as a possible indicator of the therapeutic effect: Three case reports and literature review - Lei, Yihui; Lin, Li; Cheng, Shuyu; Shao, Qiming; Ding, Chenchun; Zuo, Renjie; Chen, Weiping; Liao, Quan; Liu, Guoyan (Frontiers in Oncology, 2023)
Abstract: The posterior line treatment of unresectable advanced/metastatic gastrointestinal tumors has always been challenging point. In particular, for patients with microsatellite stable (MSS)/mismatch repair proficient (pMMR) gastrointestinal tumors, the difficulty of treatment is exacerbated by their insensitivity to immune drugs. Accordingly, finding a new comprehensive therapy to improve the treatment effect is urgent. In this study, we report the treatment histories of three patients with MMS/pMMR gastrointestinal tumors who achieved satisfactory effects by using a comprehensive treatment regimen of apatinib combined with camrelizumab and TAS-102 after failure of first- or second-line regimens. The specific contents of the treatment plan were as follows: apatinib (500 mg/d) was administered orally for 10 days, followed by camrelizumab (200 mg, ivgtt, day 1, 14 days/cycle) and TAS-102 (20 mg, oral, days 1–21, 28 days/cycle). Apatinib (500 mg/d) was maintained during treatment. Subsequently, we discussed the possible mechanism of this combination, introduced clinical trials on antiangiogenesis therapy combined with immunotherapy, and reviewed the relevant literature.